Faktor-faktor yang Mempengaruhi Kadar Gula Darah Pasien Diabetes Melitus Tipe 2 di RSU Sinar Kasih Gereja Kristen Sulawesi Tengah Tentena - Triandhini, R.L.N.K Retno; Agustina, Venti; Siabila, Yen Grasia (Jurnal Keperawatan Muhammadiyah, 2022)
Background:  Diabetes Mellitus is one of target priorities for world health problems. This is related to an increase in number of people with DM from year to year. Purpose this study is to find out the relationship of factors that affect the blood sugar levels of type 2 DM patients at RSU Sinar Kasih GKST Tentena. Method  This type of research is quantitative descriptive with a cross sectional approach implemented at RSU Sinar Kasih GKST Tentena. The intrusions used were a characteristic questionnaire of respondents, SQ-FFQ for diet and GPAQ for physical activity.  The data collected is analyzed using Microsoft excell and SPSS Discussion:  The results found blood sugar levels when patients had little difference between normal GDS levels (51.16%) and high GDS (48.83%). There is very strong correlation between IMT and GDS while for RLPP with GDS does not have significant correlation between the two variables. The food group that had meaningful correlation with the GDS was the oil and fat group as well as for physical activity and the GDS had meaningful correlation with direction of the negative correlation. Conclusion this study is factors that have an association in influencing blood sugar levels of type 2 DM patients in RSU Sinar Kasih Christian Church of Central Sulawesi Tentena are BMI, diet and physical activity while for RLPP does not have significant association to blood sugar levels of type 2 DM patients.